2002
DOI: 10.1128/aem.68.9.4694-4697.2002
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Sinorhizobium meliloti from the Central Asian Alfalfa Gene Center

Abstract: Sinorhizobium meliloti was isolated from nodules and soil from western Tajikistan, a center of diversity of the host plants (Medicago, Melilotus, and Trigonella species). There was evidence of recombination, but significant disequilibrium, between and within the chromosome and megaplasmids. The most frequent alleles matched those in the published genome sequence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 16 publications
(6 reference statements)
2
29
1
1
Order By: Relevance
“…Indeed, several studies of natural populations of S. meliloti (13,26) identified evidence for recombination. Our analysis of novel DNA sequence distribution is consistent with these studies and suggests that natural populations of S. meliloti have a predominantly clonal population structure with low-level genetic recombination ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies of natural populations of S. meliloti (13,26) identified evidence for recombination. Our analysis of novel DNA sequence distribution is consistent with these studies and suggests that natural populations of S. meliloti have a predominantly clonal population structure with low-level genetic recombination ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…This bacterial diversity, assessed by phenotypic or genotypic analyses, has been reported to be influenced by several factors, including geographical location (32), soil factors (14), and plant species (19,37). Furthermore, at an interspecies level, several studies on S. meliloti and S. medicae natural populations, trapped from various soils (using several Medicago species), reported either the balanced coexistence of the two bacterial species (3,23) or the dominance of one of them (3,31,33,43).At a plant genotype level, host nodulation specificity could also influence the bacterial diversity in soil. Significant variations were detected among rhizobial populations associated with different plant lines of Vicia faba (38), Pisum sativum (10), or Medicago sativa (26).…”
mentioning
confidence: 99%
“…Prior to the S. meliloti Rm1021 sequencing project, there was already interest in genes located on accessory plasmids. Population analysis revealed that some plasmids are widespread in indigenous rhizobial populations and occur at frequencies of at least 50% (1,4,56). It is assumed that rhizobial accessory plasmids are interchangeable among indigenous rhizobial populations.…”
mentioning
confidence: 99%